1969
DOI: 10.1111/j.1432-1033.1969.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Vitamin A Acetate by Unspecific Carboxylesterases from Liver and Kidney

Abstract: Vitamin A acetate is hydrolysed by highly purified carboxylesterases (EC 3.1.1.1) from liver and kidney of several species (pig, ox, man), whereas long-chain fatty acid esters of vitamin A are not split. [7,8]. The substrate specifity of these carboxylesterases is remarkably low. Observations of Frimmer and Gries [9] gave first indications that vitamin A acetatc is hydrolysed by pig liver esterase. In the present communication this reaction has been characterized in more detail by experiments on the enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1973
1973
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The specific activities of the rat liver esterases for the hydrolysis of retinyl acetate are about 10-fold lower than those reported by Bertram & Krisch [3] for pig liver esterase. It is not clear whether their pig liver esterase preparation really lacked retinyl palmitate hydrolase activity or whether their measurement was not sensitive enough.…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…The specific activities of the rat liver esterases for the hydrolysis of retinyl acetate are about 10-fold lower than those reported by Bertram & Krisch [3] for pig liver esterase. It is not clear whether their pig liver esterase preparation really lacked retinyl palmitate hydrolase activity or whether their measurement was not sensitive enough.…”
Section: Resultscontrasting
confidence: 58%
“…Several attempts have been undertaken to ascertain such functions from their possible activity on physiological ester-type lipids. In 1969, Bertram & Krisch [3] demonstrated that vitamin A acetate is a substrate for purified pig, ox and human liver esterases. As a result, the Nomenclature Committee of the International Union of Biochemistry deleted the entry EC 3.1.1.12 (vitamin A esterase) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, purified carboxylesterase (EC 3.1.1.1) from rat serum has been reported to be very sensitive to DFP but not to PCMB or eserine (Hashinotsume et al, 1978). Furthermore, highly purified carboxylesterases (EC 3.1.1.1) from liver and kidney of several species hydrolyze vitamin A acetate, but not vitamin A palmitate, stearate, and oleate in vitro (Bertram and Krisch, 1969), regardless of the storage in the liver of these long-chain fatty acid esters of vitamin A. Highly purified carboxylesterases are inhbited by 10 p,M E 600 but not by eserine or PCMB (Bertram and Krisch, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, highly purified carboxylesterases (EC 3.1.1.1) from liver and kidney of several species hydrolyze vitamin A acetate, but not vitamin A palmitate, stearate, and oleate in vitro (Bertram and Krisch, 1969), regardless of the storage in the liver of these long-chain fatty acid esters of vitamin A. Highly purified carboxylesterases are inhbited by 10 p,M E 600 but not by eserine or PCMB (Bertram and Krisch, 1969). Lipid droplets in mouse hepatocytes have been demonstrated to be positive for esterase activity, as revealed by using 8-actoxy-quinoline as a substrate.…”
Section: Discussionmentioning
confidence: 99%